Penerapan Sistem Manajemen Mutu ISO 9001: 2015 dalam Mendukung dan Menunjang Pemasaran Produk: Narrative Literatur Review - Azfa, Muhammad Farhan; Solihah, Riri Hilmatus (AGUSPATI RESEARCH INSTITUTA, 2024)
In faing global competition, of coures consumen awareness is increasing on product quality, therefore companies neede to pay attention to the quality of the products they produce. The consistent implementation of a quality management system affects product quality and costumer satisfaction. The standard dor international quality management that is commonly used is ISO 9001:2015, for this reason, companies need to receive international recognition stating that the product and systems used comply with the standards. Marketing management plays and important role in implementing the system to determine market conditions and demands as well as designing strategies to achieve company targets. This study aims to analyze and determine the effect of implementing a quality management system in supporting marketing activities and the supporting and inhibiting factors for its application. The type of research used is descriptive and analyze using quantitative methods. The data collection technique was carried out in the manner proposed according to the table for the implementation of ISO 9001:2015 in marketing.